Uptake of iron oxide nanoparticles inhibits the photosynthesis of the wheat after foliar exposure. (November 2020) - Lu, Kun; Shen, Danlei; Liu, Xiaokai; Dong, Shipeng; Jing, Xueping; Wu, Wei; Tong, Yang; Gao, Shixiang; Mao, Liang
Abstract: Iron oxide nanoparticles (nFe2 O3 )-filled materials have been widely employed in various products and their effects on plants have attracted considerable attention because of their potential release into the environment. Currently, numerous studies reporting the influences of iron-bearing nanoparticles on plants are focused on root or seed exposure. However, plants exposed to atmospheric iron-bearing nanoparticles through the leaves and their impacts on plants are still not well understood. This study focused on the uptake, translocation, and effects of foliar exposure of nFe2 O3 on wheat seedlings. Wheat seedlings were foliar applied to various concentrations of nFe2 O3 (0, 60 and 180 μg per plant) for 1, 7, 14 or 21 d. Our results demonstrated that after exposure for 21 d, the concentrations of Fe in leaves, stems, and roots were 1100, 280 and 160 μg kg −1, respectively. Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), as well as the backscattered electron (BSE) images, revealed the stomatal opening was likely the pathway for nFe2 O3 uptake. Analysis of the transfer rate, translocation of Fe from leaves to stems and roots, suggested the involvement of plant Fe regulation processes. Particularly, the antioxidant enzymatic activities and malondialdehyde levels in leaves were modified, which was ascribed to the excessive hydroxyl radical (OH) generated via the Fenton-like reaction mediated by nFe2 O3 . Finally, the OH facilitated the degradation of chlorophyll, posting a negative impact on the photosynthesis, and thus inhibited the biomass production. These findings are meaningful to understand the fate and physiological effects of atmospheric nFe2 O3 in crops. Graphical abstract: Image 1 Highlights: nFe2 O3 was accumulated in the wheat after foliar exposure. nFe2 O3 triggered the Fenton-like reaction and generated excessive OH. nFe2 O3 disturbed the redox homeostasis and thereby caused oxidative stress. The excessive OH facilitated the degradation of chlorophyll, thus inhibited plant growth.